Patterns and drivers of long term spatio-temporal change in a rural savanna landscape - Saunders, James Fabian (My University, 2016)
Ecosystem services provide a vital lifeline to millions of people living in rural areas. The poorest people in these areas depend upon the natural resource base in their surroundings to provide these services. With growing populations in rural areas of South Africa, the natural resource base is under considerable pressure; however, uncovering the dynamics of vegetation in these systems has proven difficult. While much attention has been given to savanna ecology, long term studies on the patterns and drivers of woody biomass are few. We used 65 years of aerial imagery (from 1944 to 2009) over 31 953 ha of rural savanna in a communal rangeland in South Africa to determine the abundance of woody canopy cover. This data were captured at hectare resolution, giving a fine enough level of detail for local level analysis. We also captured data for five potential drivers for change at this resolution, in order to analyse these drivers for their relative importance in determining woody canopy cover throughout the study period. Surprisingly, while individual sites showed varied trends in the amounts of woody canopy cover through time, when pooled across all sites the total woody canopy cover increased over the 65 year period. Disturbance gradients were found around some of the villages, but only in 2009, suggesting that the drivers of disturbance gradients in these systems may have only operated sufficiently to produce disturbance gradients in recent years. A hot spot analysis (hot spots indicate cells that have similarly high values beyond what would be expected in a random distribution, with cold spots indicating the inverse) revealed an increase in both hot and cold spots through time, but with a low persistence of both through time. High canopy cover cells are presumed to be the result of bush encroachment, while low canopy cover cells are presumed to be the result of harvesting of trees for fuelwood or clearing for fields. The low persistence of hot and cold spots points to a system in continual change, with patches of hot and cold spots appearing and disappearing, and therefore drivers of change operating in short periods of time. MAP (Mean Annual Precipitation), and not an anthropogenic driver, was found to be the most important driver for woody canopy cover throughout the study period, with MAP up to 670 mm having a predictable pattern of hot and cold spots through time. Higher MAP was shown to have a non-linear and unpredictable pattern of hot and cold spots through time, indicating that low precipitation may produce a system where woody canopy cover is less influenced by other drivers and is more stable when acted upon by other drivers. This research demonstrates the value of a long term dataset, and the applicability of our methods for monitoring woody canopy cover. As such, it may well serve as a baseline for woody canopy cover in communal savanna rangeland systems, with the methodology employed here suitable for an early warning detection system for sudden changes in the woody canopy cover.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Science 17th August 2015 in Johannesburg, South Africa
Keywords: Savanna ecology.; Plant biomass.; Biomass energy--South Africa.